Specialist palliative and end-of-life care for patients with cancer and SARS-CoV-2 infection: a European perspective. (September 2021) - Soosaipillai, Gehan; Wu, Anjui; Dettorre, Gino M; Diamantis, Nikolaos; Chester, John; Moss, Charlotte; Aguilar-Company, Juan; Bower, Mark; Sng, Christopher CT; Salazar, Ramon; Brunet, Joan; Jones, Eleanor; et al.
Background: Specialist palliative care team (SPCT) involvement has been shown to improve symptom control and end-of-life care for patients with cancer, but little is known as to how these have been impacted by the COVID-19 pandemic. Here, we report SPCT involvement during the first wave of the pandemic and compare outcomes for patients with cancer who received and did not receive SPCT input from multiple European cancer centres. Methods: From the OnCovid repository ( N  = 1318), we analysed cancer patients aged ⩾18 diagnosed with COVID-19 between 26 February and 22 June 2020 who had complete specialist palliative care team data (SPCT+ referred; SPCT− not referred). Results: Of 555 eligible patients, 317 were male (57.1%), with a median age of 70 years (IQR 20). At COVID-19 diagnosis, 44.7% were on anti-cancer therapy and 53.3% had ⩾1 co-morbidity. Two hundred and six patients received SPCT input for symptom control (80.1%), psychological support (54.4%) and/or advance care planning (51%). SPCT+ patients had more 'Do not attempt cardio-pulmonary resuscitation' orders completed prior to (12.6% versus 3.7%) and during admission (50% versus 22.1%, p  < 0.001), with more SPCT+ patients deemed suitable for treatment escalation (50% versus 22.1%, p  < 0.001). SPCT involvement was associated with higher discharge rates from hospital for end-of-life care (9.7% versus 0%, p  < 0.001). End-of-life anticipatory prescribing was higher in SPCT+ patients, with opioids (96.3% versus 47.1%) and benzodiazepines (82.9% versus 41.2%) being used frequently for symptom control. Conclusion: SPCT referral facilitated symptom control, emergency care and discharge planning, as well as high rates of referral for psychological support than previously reported. Our study highlighted the critical need of SPCTs for patients with cancer during the pandemic and should inform service planning for this population.